Contemporary Methods for Capturing Juvenile Salmonids in the Marine Environment - Sean C. Godwin; Emma M. Atkinson; Jamieson B. Atkinson; Mackenzie C. Bartlett; William D. P. Duguid; Marc Trudel; Andrew W. Bateman (Fish and Fisheries, 2026)
Anadromous salmonids play vital roles in marine and freshwater ecosystems. The most abundant of these fishes—Pacific salmon ( Oncorhynchus spp.)—are integral to coastal ecosystems and communities across the North Pacific Rim, but numerous populations are experiencing dramatic declines, particularly towards the south of their range. Although many declines have been linked to poor marine survival, the early marine life phase of salmon has historically been difficult to study because of challenges in capturing juvenile salmon once they leave freshwater. Recent advancements in capture methods, refined over decades of research, have greatly expanded our understanding of juvenile Pacific salmon life history. Here, we synthesise and review the literature on the five main capture techniques for juvenile Pacific salmon in the marine environment: beach seine, miniature purse seine, conventional purse seine, microtroll, and rope trawl. We compare gear, selectivity, cost, and fish welfare considerations across methods. Along with demonstrated utility in Pacific salmon research, these methods also have broad—and in some cases unexplored—applicability for studying other salmonids and nearshore marine fishes globally, including invasive populations and Atlantic salmon.

Oust the louse: leaping behaviour removes sea lice from wild juvenile sockeye salmon Oncorhynchus nerka - Emma M. Atkinson; Andrew W. Bateman; Lawrence M. Dill; Martin Krkošek; John D. Reynolds; Sean C. Godwin (Journal of Fish Biology, 2018)
We conducted a manipulative field experiment to determine whether the leaping behaviour of wild juvenile sockeye salmon Oncorhynchus nerka dislodges ectoparasitic sea lice Caligus clemensi and Lepeophtheirus salmonis by comparing sea‐lice abundances between O. nerka juveniles prevented from leaping and juveniles allowed to leap at a natural frequency. Juvenile O. nerka allowed to leap had consistently fewer sea lice after the experiment than fish that were prevented from leaping. Combined with past research, these results imply potential costs due to parasitism and indicate that the leaping behaviour of juvenile O. nerka does, in fact, dislodge sea lice.